The arts and copyright (WIPO GenevaCH, 2007)
Provides basic information about copyright and related rights. Seeks to show students how they can find and use works in the public domain. Explains three common types of copyright infringement and how they can be avoided. Deals with the challenges that digital technology presents to the protection of copyrighted works.
Bibliography: p. 70